ANALISIS SISTEM PENGADAAN PROYEK KONSTRUKSI TERHADAP PENYERAPAN ANGGARAN PEMERINTAH KABUPATEN BADUNG - N. Gita Astadi; I N. Sutarja; Mayun Nadiasa (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2015)
Abstract : The rate of absorption of a government budget, especially on the construction projects, determine whether or not the optimal development of a region. The faster the budget absorption of the construction projects, the faster the perceived benefits. The purpose of the study was to determine the rate of the budget absorption, to find out the factors in the construction project procurement systems that affect the slow budget absorption of the Local Government of the Badung Regency as well as the efforts to minimize such delays. The data were obtained from the parties involved in the procurement of the construction projects through questionnaires as the research instruments. In addition, the data were also obtained through interviews, observations and documentations. The variables used in the study were 38 variables and 60 persons as the respondents. The data analysis was conducted through descriptive analysis, absorption analysis and factor analysis. The scoring system used a Likert scale, and data processing was conducted by SPSS. The findings of the study show that the rate of absorption of the Badung Regency Government’s construction projects for Fiscal Year 2012 - 2013 was not in accordance with the plan, but the increase was more than that of the previous fiscal year. While the results of the factor analysis by using SPSS indicate that the factors that affecting the slow absorption budget in the procurement system of most construction projects are: the fear and caution of the parties in carrying out procurement activities, the change in the activity package, the slow preparation of the Owner's Estimate (OE), the incomplete procurement documents, the misrepresentation of the procurement regulations and the slow process of procurements. And the most effective effort to enhance the budget absorption are the determination of the communication standards, the coordination and the synchronization in the procurement of construction projects with all parties involved in the procurement systems.